Analisis Kesalahan Siswa MTs dalam Menyelesaikan Soal-Soal Aljabar Menggunakan Teori Newman - Aswan, Aswan; Pratiwi Putri, Dina Eki; Prayoga, Hanna Arsyinta; Oktavi, Nadia Silmi (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2024)
This research was conducted to analyze students' errors in solving junior high school algebra problems and the causes of these errors using Newman's theory. This research uses a quantitative descriptive approach. The research subjects were 31 class VII students. The instrument of this research is written formative test questions on algebra topics which are analyzed using Newman error analysis. Based on the results of data analysis, it was concluded that students made (1) mistakes in reading the questions; (2) mistakes in understanding the questions; (3) process skills errors, and (4) errors in writing final answers. Based on the research results, it can be concluded that based on Newman's theory, there are four mistakes made by junior high school students in solving algebra problems Keywords: student errors, Newman Theory, algebra